THE ROLE OF RUSSIAN ORIENTALISTS IN STUDYING THE EDUCATIONAL SYSTEM OF THE KOKAND KHANATE IN THE PERIOD OF THE RUSSIAN EMPIRE - Mukhammadjon Odiljon ugli Alikhojiev (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the works of Russian orientalists who made a significant contribution to the study of the education system in the Kokand Khanate. The article also analyzed during the period of colonization of Turkestan by the Russian Empire (1867-1917), the work was mainly carried out by administrators-orientalists and local historians who functioned on the territory of the region, whose main goal was to study the education system and regulate it through reforms.